Automated workflow for the cell cycle analysis of (non-)adherent cells using a machine learning approach - Kourosh Hayatigolkhatmi; Chiara Soriani; Emanuel Soda; Elena Ceccacci; Oualid El Menna; Sebastiano Peri; Ivan Negrelli; Giacomo Bertolini; Gian Martino Franchi; Roberta Carbone; Saverio Minucci; Simona Rodighiero (eLife)
Understanding the cell cycle at the single-cell level is crucial for cellular biology and cancer research. While current methods using fluorescent markers have improved the study of adherent cells, non-adherent cells remain challenging. In this study, we addressed this gap by combining a specialized surface to enhance cell attachment, the FUCCI(CA)2 sensor, an automated image analysis pipeline, and a custom machine learning algorithm. This approach enabled precise measurement of cell cycle phase durations in non-adherent cells. This method was validated in acute myeloid leukemia cell lines NB4 and Kasumi-1, which have unique cell cycle characteristics, and we tested the impact of cell cycle-modulating drugs on NB4 cells. Our cell cycle analysis system, which is also compatible with adherent cells, is fully automated and freely available, providing detailed insights from hundreds of cells under various conditions. This report presents a valuable tool for advancing cancer research and drug development by enabling comprehensive, automated cell cycle analysis in both adherent and non-adherent cells.